Detection of Potential Fire Hazard Points in Electrical Networks Using Thermal Cameras and Their Mapping - Αποστολίδης Απόστολος - Μάξιμος; Επιβλέπων εκπαιδευτικός Κοσμάς Αδαμίδης (Open Schools Journal for Open Science, 2025)
This project aims to develop an advanced system for detecting potential fire hazard points along power transmission networks using thermal cameras and GPS technology. Focusing on areas where transmission lines are close to vegetation, the objective is to create a comprehensive risk map that will assist utility companies and authorities in preventive maintenance and fire mitigation efforts. Thermal cameras capable of detecting temperature anomalies indicative of overheating will be mounted on unmanned aerial vehicles or other mobile units to inspect the network. These cameras will record real-time temperature data, identifying sensitive points. Simultaneously, GPS coordinates will be logged for each identified hazard point. In addition to recording thermal anomalies, this project will utilize a Geographic Information System (GIS) to visualize the spatial distribution of these risks and map them.